Där monumenten står i vägen - Frykman, Jonas (Tidsskrift for kulturforskning, 2007)
This is a study of how socialist monuments in Croatian Istria are ending up in cultural brackets. When the region today is constructing its cultural identity, these monuments belong to the parts of material culture that are inert, and averse. Delineating a territory that no longer exists, an ideology that is severely contested and a rump Yugoslavia that in the 90s was becoming a threat to the new nation - they are ending up in a cultural limbo. Other parts of the past - even the fictional like the one described in the novel Mathias Sandorf by Jules Verne - have proven to be more useful in creating a legacy for the present. The partisan monuments thus help to exclude the part of history, of which most adults have direct memories. It is argued that cultural identity is a future oriented process that is carefully selecting its memories.